PENENTUAN INDEKS IKLIM MENGGUNAKAN METODE HISTORICAL BURN ANALYSIS UNTUK ASURANSI PERTANIAN DI KABUPATEN BREBES - Hasalika Nurjannah; Agus Safril (Jurnal Meteorologi Klimatologi dan Geofisika, 2020)
Agricultural insurance is a form of adaptation that farmers can do to deal with extreme climate such as drought. Climate index insurance is one of agricultural insurance that uses climate parameter to determine payment for farmers. Climate parameter which is used in this analysis is rainfall and conducted in Brebes Regency. The analysis uses rainfall data in millimeters (mm) during decade days that calculated in area which has same rainfall pattern called ZOM, from 2008 to 2018. The result of climate index analysis using Historical Burn Analysis produce two values, namely trigger value and exit value. Trigger and exit value determine how much payment for the insurance claim based on rainfall data, which trigger is the threshold for the payment of insurance claim while exit value is the threshold for full payment. The results showed that in ZOM 95 trigger value is 18.7 mm and exit value is 4 mm, in ZOM 96 trigger value is 18.3 mm and exit value is 1.3 mm, in ZOM 97 trigger value is 19.8 mm and exit index is 3.5 mm, in ZOM 103 trigger value is 14.8 mm and exit value is 3.0 mm, in ZOM 105 trigger value is 26.3 mm and exit value is 8.0 mm. The value of trigger and exit is valid in window period, which starts from July to September.